Role of reductant for generation of solar energy in photogalvanic cell - Chandra, Mahesh; Meena, RC (BIBECHANA, 2010)
The Photo voltages and photocurrents in photo galvanic cell containing a dye Rose Bengal and Oxalic Acid as reducing agent have been determined. The photo-outputs with Oxalic Acid are higher than Rose Bengal and Mannitol system. The efficiency of the Rose Bengal –Oxalic Acid photo galvanic cell has been estimated to be 0.981%. The photo potentials and photocurrent garneted, conversion efficiency, power of the cell and cell performance of the photo galvanic cells were determined. The effects of different parameters on electrical output of the cell were observed. A mechanism has also been proposed for the generation of the photocurrent in photo galvanic cell. Keywords: Photo galvanic cell; Photopotential; Rose Bengal; Oxalic acid,; Mannitol; Power point DOI: 10.3126/bibechana.v7i0.4036 BIBECHANA 7 (2011) 6-13